Análisis de la aplicabilidad de la guía GTC-180 sobre responsabilidad social en la Sala Administrativa del Consejo Superior de la Judicatura (2010)
This article shows the results of a research carried out in the Administrative Chamber of the Supreme Judicial Council to identify the applicability of the social responsibility aspects given by Colombian GTC-180. The processing of various types of surveys that were given to the officials of different hierarchical levels of the Chamber, which were developed by reference to the GTC-180, was initially used as a methodology for gathering information. The analyses of this data led to preliminary conclusions that were discussed with three experts in social responsibility in the country, to extract definitive conclusions. The results showed that social responsibility is indispensable for the management of the Administrative Chamber of the Supreme Judicial Council, particularly in matters related to the respect of civil rights, ethical issues (including the principles and management value, the development of the code of ethics and practices against corruption) and corporate goverment